Analisis Budaya Organisasi dan Program Retensi terhadap Kinerja Tenaga Pendidik pada Masa COVID-19 - Ardi Juanda; Tatan Sukwika; Kholil Kholil (Jurnal Manajemen dan Organisasi, 2023)
The national education standard index for three years at SIT Insantama in Banten Province tends to rise. However, since the COVID-19 outbreak, the index value has decreased. This study aimed to analyze the effect of organizational culture variables and retention programs on the performance of educators through the engagement of educators. The quantitative approach method is based on data sourced from questionnaires and observations are used. Data processing is assisted by SmartPLS software. The research population of 80 people is all SIT Insantama educators in Banten Province which are located in three locations, namely Serang City, Cilegon City and Rangkasbitung Regency. The results of the analysis show that organizational culture has a negative and insignificant effect on the performance of educators, the retention program has a positive but not significant effect on the performance of educators. Other findings show that retention programs and organizational culture have a positive and significant effect on the engagement of educators. The engagement of educators also has a positive and significant effect on the performance as well as the engagement of educators. These findings provide guidelines for management to improve the implementation of organizational culture and management of retention programs, in order to have a better impact on the performance of educators in addition to strengthening the engagement of educators.